SCIENTIFIC AND THEORETICAL BASIS OF COLD CHAIN INFRASTRUCTURE IN THE PROCESS OF INCREASING THE ADDITIONAL VALUE OF FRUIT AND VEGETABLE PRODUCTS - Saidova, Gulnoza Tulkunovna (THE INNOVATION ECONOMY, 2026)
This article examines the role and importance of cold chain infrastructure in increasing the added value of fruits and vegetables. It analyzes the cost-effectiveness of temperature control systems in fruit and vegetable processing, from cultivation to delivery to the consumer. The results suggest that the implementation of cold chain infrastructure reduces product loss, extends shelf life, and increases export potential.